Dampak Broken Home terhadap Kemampuan Psikomotorik Siswa SDN 1 Hadiluwih - Anam, M Khoirul; Al-Fath, Ayatullah Muhammadiin; Ardhyantama, Vit (PGSD STKIP PGRI Pacitan, 2022)
This study aims to find out 1) The condition of the broken home students in terms of their psychomotor aspects at SDN 1 Hadiluwih, (2) The difference between students who are victims of a broken home in the psychomotor aspects of students affected by a broken home at SDN 1 Hadiluwih, (3) Describe the steps for handling and development of psychomotor aspects of students who are victims of broken homes at SDN 1 Hadiluwih. This research is a qualitative research using a descriptive approach. The data collection instruments used in this study were observation, interviews and documentation. The data collection instrument was used to find out how the impact of students who experienced broken home victims in their families and how the role of parents in improving their psychomotor abilities. The validity of the data used triangulation and continued with data analysis using the Miles and Huberman model. The results showed that: 1) Children with a broken home and children without a broken home did not have a significant difference in their psychomotor aspects, (2) The results of interviews with 3 affected out of 8 students showed that on average children experienced the same activities during the learning process. at home or at school, and receive special attention from teachers and parents for learning and advice, (3) Efforts made by teachers and families to students affected by a broken home are mutual support and complement, so that students do not feel alone in activities related to still in psychomotor abilities.